Implementasi Konsep Geometri dan Teori Graf dalam Permainan Tradisional Gobak Sodor - Panjaitan, Sorta Corie Ivana; Fauzi, Muhhammad Amin; Sitompul, Pardomuan (Jurnal Didaktika Pendidikan Dasar, 2025)
Traditional games can be a means of learning and character building. In the traditional game Gobak Sodor there is an educational element. Through the game Gobak Sodor the character values of the players can be developed. The Gobak Sodor game can be created to improve understanding of Mathematics subjects, moreover, by applying mathematics during the game, the chances of winning the game are greater. This study aims to explain the mathematical concepts related to Geometry and Graphs applied to the gobak sodor game at SMP Negeri 3 Jorlang Hataran, Simalungun Regency. This study is a qualitative study. Likewise, understanding the concepts of points, lines, area and perimeter in flate shapes (square, rectangle, and circle) related to the length of the player’s hand or reach, as well as position on the field can increase the chances of winning the game. Apart from that, by using graph theory you can see opportunities, look for the shortest route while still avoiding your opponent’s touch to get points.